ACOUSTIC ASSESSMENT OF FLOW PATTERNS IN UNSATURATED SOIL - Flammer I.; Blum A.; Leiser A.; Germann P. (My University, 2001)
Acoustic wavelengths in soils range from meters to millimeters, depending on their frequencies. The spatial and temporal scales of pulse transmission through soils are well suited to investigate transient and presumably heterogeneous water infiltration into and redistribution within soils.Acoustic pulses were transmitted through a column of an undisturbed and partially water-saturated loess soil with height and diameter of 0.8 and 0.3 m, respectively. The maximum frequency of the arriving pulses was 10 kHz, which corresponds to a wavelength of about 50 mm. Both travel velocities and absorption of the acoustic waves reacted in the expected ways on soil moisture variations; however, the two temporal reaction patterns differed considerably. Brutsaert's [J. Geophys. Res. 69 (1964) 243] model was successfully applied to the data. Dye tracers visualized the patterns of water distribution. Their scale compares well with theoretical considerations on the flow paths and the results from the acoustic investigations.
Keywords: ACOUSTIC WAVES; BULK MODULUS; POROUS MATERIALS; PREFERENTIAL FLOW